Early metabolic development of posteromedial cortex and thalamus in humans analyzed via in vivo quantitative magnetic resonance spectroscopy. Issue 16 (10th July 2014) - Degnan, Andrew J.; Ceschin, Rafael; Lee, Vince; Schmithorst, Vincent J.; Blüml, Stefan; Panigrahy, Ashok
ABSTRACT The posteromedial cortex (PMC) including the posterior cingulate, retrosplenial cortex, and medial parietal cortex/precuneus is an epicenter of cortical interactions in a wide spectrum of neural activity. Anatomic connections between PMC and thalamic components have been established in animal studies, but similar studies do not exist for the fetal and neonatal period. Magnetic resonance spectroscopy (MRS) allows for noninvasive measurement of metabolites in early development. Using single‐voxel 3‐T MRS, healthy term neonates (n = 31, mean postconception age 41.5 weeks ± 3.8 weeks) were compared with control children (n = 23, mean age 9.4 years ± 5.1 years) and young adults (n = 10, mean age 24.1 years ± 2.6 years). LCModel‐based calculations compared metabolites within medial parietal gray matter (colocalizing to the PMC), posterior thalamus, and parietal white matter voxels. Common metabolic changes existed for neuronal−axonal maturation and structural markers in the PMC, thalamus, and parietal white matter with increasing NAA and glutamate and decreasing myoinositol and choline with age. Key differences in creatine and glucose metabolism were noted in the PMC, in contrast to the thalamic and parietal white matter locations, suggesting a unique role of energy metabolism. Significant parallel metabolite developmental changes of multiple other metabolites including aspartate, glutamine, and glutathione with age were present between PMC and parietal white matter but not between PMC and thalamus. These findings offer insight into the metabolic architecture of the interface between structural and functional topology of brain networks. Further investigation unifying metabolic changes with functional and anatomic pathways may further enhance the understanding of the PMC in posterior default mode network development. J. Comp. Neurol. 522:3717–3732, 2014. © 2014 Wiley Periodicals, Inc.